Warriors in Winter a nonfiction companion to Magic tree house #31 - Osborne, Mary Pope; Boyce, Natalie Pope Mones, Isidre (Random House New York, 2019)
"A overview of warriors throughout history--from Ancient Greece to the Middle Ages--the equipment they used, and the most famous warriors in history"-- Provided by publisher